Identification of PPAP2B as a novel recurrent translocation partner gene of HMGA2 in lipomas. Issue 6 (18th March 2013) - Bianchini, Laurence; Birtwisle, Loïc; Saâda, Esma; Bazin, Audrey; Long, Elodie; Roussel, Jean‐François; Michiels, Jean‐François; Forest, Fabien; Dani, Christian; Myklebost, Ola; Birtwisle‐Peyrottes, Isabelle; Pedeutour, Florence
Abstract Most lipomas are characterized by translocations involving the HMGA2 gene in 12q14.3. These rearrangements lead to the fusion of HMGA2 with an ectopic sequence from the translocation chromosome partner. Only five fusion partners of HMGA2 have been identified in lipomas so far. The identification of novel fusion partners of HMGA2 is important not only for diagnosis in soft tissue tumors but also because these genes might have an oncogenic role in other tumors. We observed that t(1;12)(p32;q14) was the second most frequent translocation in our series of lipomas after t(3;12)(q28;q14.3). We detected overexpression of HMGA2 mRNA and protein in all t(1;12)(p32;q14) lipomas. We used a fluorescence in situ hybridization‐based positional cloning strategy to characterize the 1p32 breakpoint. In 11 cases, we identified PPAP2B, a member of the lipid phosphate phosphatases family as the 1p32 target gene. Reverse transcription‐polymerase chain reaction analysis followed by nucleotide sequencing of the fusion transcript indicated that HMGA2 3′ untranslated region (3′UTR) fused with exon 6 of PPAP2B in one case. In other t(1;12) cases, the breakpoint was extragenic, located in the 3′region flanking PPAP2B 3′UTR. Moreover, in one case showing a t(1;6)(p32;p21) we observed a rearrangement of PPAP2B and HMGA1, which suggests that HMGA1 might also be a fusion partner for PPAP2B. Our results also revealed that adipocytic differentiation of human mesenchymal stem cells derived from adipose tissue was associated with a significant decrease in PPAP2B mRNA expression suggesting that PPAP2B might play a role in adipogenesis. © 2013 Wiley Periodicals, Inc.